Cry1Ac and Vip3Aa proteins from Bacillus thuringiensis targeting Cry toxin resistance in Diatraea flavipennella and Elasmopalpus lignosellus from sugarcane - Lemes, Ana Rita Nunes [UNESP]; Figueiredo, Camila Soares [UNESP]; Sebastiï¿½o, Isis [UNESP]; da Silva, Liliane Marques; Alves, Rebeka da Costa; de Siqueira, Herbert ï¿½lvaro Abreu; Lemos, Manoel Victor Franco [UNESP]; Fernandes, Odair Aparecido [UNESP]; Desidï¿½rio, Janete Apparecida [UNESP] (PeerJ, 2017)
The biological potential of Vip and Cry proteins from Bacillus is well known and widely established. Thus, it is important to look for new genes showing different modes of action, selecting those with differentiated entomotoxic activity against Diatraea flavipennella and Elasmopalpus lignosellus, which are secondary pests of sugarcane. Therefore, Cry1 and Vip3 proteins were expressed in Escherichia coli, and their toxicities were evaluated based on bioassays using neonate larvae. Of those, the most toxic were Cry1Ac and Vip3Aa considering the LC50 values. Toxins from E. coli were purified, solubilized, trypsinized, and biotinylated. Brush Border Membrane Vesicles (BBMVs) were prepared from intestines of the two species to perform homologous and heterologous competition assays. The binding assays demonstrated interactions between Cry1Aa, Cry1Ac, and Vip3Aa toxins and proteins from the BBMV of D. flavipennella and E. lignosellus. Homologous competition assays demonstrated that binding to one of the BBMV proteins was specific for each toxin. Heterologous competition assays indicated that Vip3Aa was unable to compete for Cry1Ac toxin binding. Our results suggest that Cry1Ac and Vip3Aa may have potential in future production of transgenic sugarcane for control of D. flavipennella and E. lignosellus, but more research is needed on the potential antagonism or synergism of the toxins in these pests.
Keywords: Biological control; Competition assay; Insecticidal proteins